Opportunities for ovarian reserve preservation in the treatment of oncological diseases - Juliia E. Dobrokhotova; Kseniia V. Morozova (Гинекология, 2020)
This article presents the data of multi-year research on the problem of ovarian reserve preservation in cancer patients. The review includes 64 literary sources. The review provides the main methods for ovarian function preservation during the treatment of malignant diseases in patients of reproductive age. Given the increasing number of cancer patients in the group of patients of reproductive age, modern medicine is faced with the task not only to provide effective anticancer treatment, but also to try to preserve ovarian function in order to maintain hormonal levels and fertility. Unfortunately, most cancer treatment methods inhibit ovarian function. Thanks to modern approaches, there are medicinal methods for protecting against ovarian inhibition, which allows to maintain hormonal function and come back to solve reproductive problems after recovering from cancer.